India and Southeast Asia : adrift in the stormy seas? - Sinderpal, Singh (2021)
China’s growing clout and assertive behaviour have driven India closer diplomatically to Southeast Asia. However, in the last two years, two key issues have emerged, threatening to roll back India’s diplomatic gains.